2010
DOI: 10.5697/oc.52-4.621
|View full text |Cite
|
Sign up to set email alerts
|

Particulate organic carbon in the southern Baltic Sea: numerical simulations and experimental data

Abstract: The influx of solar radiation to the Baltic Sea and its penetration into its waters is described on the basis of selected results of optical and bio-optical studies in the Baltic published by various authors during the past ca 50 years. The variability in the natural irradiance of this sea is illustrated on time scales from short-term fluctuations occurring during a single day to differences in mean monthly values over a period of many years. Data on variability of the proportions between UV, * The paper was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…To a large extent, the cycle is controlled by phytoplankton activity (Dzierzbicka-Głowacka et al 2010;. To a large extent, the cycle is controlled by phytoplankton activity (Dzierzbicka-Głowacka et al 2010;.…”
Section: Factors Determining Carbon Cycle In the Marine Environmentmentioning
confidence: 99%
“…To a large extent, the cycle is controlled by phytoplankton activity (Dzierzbicka-Głowacka et al 2010;. To a large extent, the cycle is controlled by phytoplankton activity (Dzierzbicka-Głowacka et al 2010;.…”
Section: Factors Determining Carbon Cycle In the Marine Environmentmentioning
confidence: 99%
“…Results obtained by Dzierzbicka-Glowacka et al (2010) indicated that the 1-D POC model might be a useful tool for actual carbon cycle and pelagic variables investigations and prediction of theirs changes. Calibration of the model and comparison of model results with measurements for temperature and the phytoplankton biomass and nutrients concentration in 1995-2000 are given in a paper Dzierzbicka-Glowacka et al (2010). With respect to all the parameters, the correlations of the observed regularities decreased from the surface to the bottom.…”
Section: The Ecosystem Model Structurementioning
confidence: 99%
“…The different sinks and sources for 1-D POC model are put together in Table 1 in Dzierzbicka-Glowacka et al (2010), while the mathematical formulation for biogeochemical processes in the model is presented in Appendix A-C in Dzierzbicka-Glowacka (2005b) and Dzierzbicka-Glowacka et al (2010). Results obtained by Dzierzbicka-Glowacka et al (2010) indicated that the 1-D POC model might be a useful tool for actual carbon cycle and pelagic variables investigations and prediction of theirs changes.…”
Section: The Ecosystem Model Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Direct discharges of treated sewage are of importance due to the load of nutrients they carry. Increasing eutrophication also implies phytoplankton blooms, enhancing the "biological pump" phenomenon (Dzierzbicka-Głowacka et al, 2010).…”
Section: Study Areamentioning
confidence: 99%